Salam kasih dari ayahanda & kakandamu : from your father & brother - Muhammad Kamal Hassan Tan Sri 1942- (Institut Terjemahan & Buku Malaysia (ITBM), 2017)
Hereby inscribed, within the pages of this small book, the essence of what lies within my heart. Salam Kasih from your father and brother, who is craving for the mercy and compassion of his Master Rabb al-'Alamin, Al-Rahman Al-Rahim to forgive this sinful and disobedient slave of all his iniquities, injustices, faults and mistakes ... to save him, by His Infinite Mercy, from the torments of the grave, the torments of the Day of Judgement and the Torments of Hell. - M. Kamal Hassan 24 Safar 1439 / 21st March 2017